2014
DOI: 10.1007/s11432-014-5225-2
|View full text |Cite
|
Sign up to set email alerts
|

Design and aerodynamic investigation of a parallel vehicle on a wide-speed range

Abstract: In order to design a hypersonic vehicle for a wide-ranged Mach number, a novel parallel vehicle for a wide-speed range has been proposed. In this paper, we employ a numerical method to investigate a parallel vehicle's aerodynamic performance and flow field characteristics. The obtained results show that the aerodynamic performance of the novel parallel vehicle is better than that of the waverider designed with a single Mach number for the wide-speed range. With the increase in Mach number, the lift-to-drag rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…When wire rupture occurs to a certain cable, it leads to redistribution of dead and live loads that are applied to other cables and thus can endanger the whole bridge ( [5,6]. Therefore, the condition assessment of stay cables is of critical importance for cable-stayed bridges [7,8]. Cable tension monitoring is one of the widely used approaches to evaluate the health condition of bridge cables [9], which can be fulfilled by either monitoring the strain of cable wires with strain sensors or assessing the total cable forces with load cell, accelerometers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…When wire rupture occurs to a certain cable, it leads to redistribution of dead and live loads that are applied to other cables and thus can endanger the whole bridge ( [5,6]. Therefore, the condition assessment of stay cables is of critical importance for cable-stayed bridges [7,8]. Cable tension monitoring is one of the widely used approaches to evaluate the health condition of bridge cables [9], which can be fulfilled by either monitoring the strain of cable wires with strain sensors or assessing the total cable forces with load cell, accelerometers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Based on dual-cone-derived waveriders, Liu et al [16] designed a hypersonic gliding-cruising vehicle to achieve vehicle fly at two regimes. Li et al [17], [18] proposed a parallel vehicle design method and variable Mach number method for a wide-ranged Mach number to improve the overall performance of the aircraft. Zhao et al [19] put forwards a variable Mach number design approach based on the osculating cone theory and found that the waverider had superior low-speed aerodynamic performance and high-speed aerodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…This configuration was proved to have strong adaptability in a wide speed range. Li et al [40,41] proposed a parallel vehicle for a wide-speed range and a hypersonic vehicle in tandem based on the cone-derived method. They studied the aerodynamic performance of these vehicles and proved that both of them have good aerodynamic performance.…”
Section: Introductionmentioning
confidence: 99%